Initial impacts of the COVID-19 pandemic on the Canadian labour market - Thomas Lemieux; Kevin Milligan; Tammy Schirle; Mikal Skuterud (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
In this study we review the initial impacts of the COVID-19 pandemic on the Canadian labour market. We focus on changes in employment and aggregate hours worked between February 2020 and April 2020, while accounting for normal monthly changes in these indicators. We find that COVID-19 induced a 32 percent decline in aggregate weekly work hours among workers aged 20-64, alongside a 15 percent decline in employment. We characterize the distribution of work lost, finding that nearly half of job losses are attributed to workers in the bottom earnings quartile. Those most impacted by COVID-19 are in public-facing jobs in industries most affected by shutdowns (accommodation and food services), are younger workers, paid hourly, and nonunion. The results provide context for policy development, with both supply and demand sides of the labour market to consider.
Keywords: 330; COVID-19; employment; wages; work hours; unemployment